Policing and prosecuting sexual assault: inside the criminal justice system - Spohn, Cassia (Lynne Rienner Publishers, 2013)
Sexual assault and the criminal justice system -- Policies and practices -- Detective and prosecutor perspectives -- Case attrition and case outcomes -- False reports -- The overuse and misuse of the exceptional clearance -- Intimate partner sexual assault -- Taking sexual assault seriously -- References